PENGARUH MOTIVASI DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA PT BPD KALTIM KALTARA CABANG UTAMA DI SAMARINDA - Siti Muliana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This research was conducted at one of the banks in the city of Samarinda. Based on the interview results, there are several employees who are dissatisfied with what they have received from the company, the company must continue to pay attention to the level of workload and provide continuous motivation to every employee without favoritism so that employees feel sufficient and satisfied for what they have received . This type of research is quantitative research. This research method uses multiple linear regression analysis methods. The results of data processing showed that the regression results were Y = 0.328 + 0.733 X1 + 0.163 X2, showing Motivation (X1) 0.733 and workload (X2) 0.163 and obtained a correlation coefficient of 0.794 or 79.4% and a coefficient of determination of 0.63 or 63%. The results of simultaneous hypothesis research (Test F) by obtaining Fcount 69.892 with Ftable of 3.108, thus proving a significant effect on employee job satisfaction. The results of partial hypothesis testing (T test) are known that motivation is the most influential variable on employee job satisfaction and with the acquisition of Tcount of 9.3362 with Ttable 1.989, thus proving a significant effect on employee job satisfaction. The most influential hypothesis research results are known that motivation is the most influential variable that is most influential on employee job satisfaction with the acquisition of standardized regression coefficients (Standardized coefficients) of 0.688 greater than the variable Workload of 0.205 then proves significant effect on employee job satisfaction. Suggestions for companies to be able to provide bonuses for employees who have shown good and satisfying performance and performance, but also can provide direction or guidance for employees who have not been given before or work with a high degree of difficulty.